Development Of Folk Oral Creativity In The Kashkadarya Region - Murodova Sadoqat Qoziboyevna (Euro Asian Journal Publishing, 2024)
This article reveals the role of traditional performance in the folklore of the Kashkadarya oasis, as well as badihagoy, epic, askiya
Keywords: folklore; creativity; tradition